Fools and mortals [compact disc, unabridged] : a novel - Cornwell, Bernard (Harper Audio, 2018)
When a priceless manuscript goes missing, suspicion falls on Richard Shakespeare, the estranged brother of the famous author, forcing him down a perilous path through London.